African Initiated Christianity and the Decolonisation of Development Sustainable Development in Pentecostal and Independent Churches - Öhlmann, Philipp (Routledge Research in Religion and Development, 2020)
This book investigates the substantial and growing contribution which African Independent and Pentecostal Churches are making to sustainable development in all its manifold forms. Moreover, this volume seeks to elucidate how these churches reshape the very notion of sustainable development and contribute to the decolonisation of development. Fostering both overarching and comparative perspectives, the book includes chapters on West Africa (Nigeria, Ghana, and Burkina Faso) and Southern Africa (Zimbabwe and South Africa). It aims to open up a subfield focused on African Initiated Christianity within the religion and development discourse, substantially broadening the scope of the existing literature.